FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Reyliani Aprilia; Nur Cahyonowati (Diponegoro Journal of Accounting, 2022)
This study aims to obtain empirical evidence and analyze the effect of firm size, profitability, solvency, KAP size, audit opinion, audit committee, and subsequent events on audit delay. Property and real estate companies in 2017-2020 are the population used in this research. The research sample was selected using purposive sampling method with a total sample of 130 units of analysis. The analytical technique used in this research is multiple regression analysis.The results obtained from this study indicate that profitability and audit opinion have a negative effect on audit delay, while subsequent events have a positive effect on audit delay. Firm size, solvency, KAP size, and audit committee have no effect on audit delay.